1998
DOI: 10.1086/301761
|View full text |Cite
|
Sign up to set email alerts
|

A Human Homologue of the Drosophila melanogaster diaphanous Gene Is Disrupted in a Patient with Premature Ovarian Failure: Evidence for Conserved Function in Oogenesis and Implications for Human Sterility

Abstract: Premature ovarian failure (POF) is a defect of ovarian development and is characterized by primary or secondary amenorrhea, with elevated levels of serum gonadotropins, or by early menopause. The disorder has been attributed to various causes, including rearrangements of a large "critical region" in the long arm of the X chromosome. Here we report identification, in a family with POF, of a gene that is disrupted by a breakpoint. The gene is the human homologue of the Drosophila melanogaster diaphanous gene; mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
152
0
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(160 citation statements)
references
References 26 publications
2
152
0
6
Order By: Relevance
“…The upstream diaphanous (DIAPH) genes accelerate actin nucleation and suppress actin depolymerization. Of interest, disruption of the DIAPH2 coding region was found in a POI family (31), whereas genome-wide association studies identified DIAPH2 (32) and DIAPH3 (33) as candidate genes in regulating follicle reserve and menopause (Fig. S7).…”
Section: Discussionmentioning
confidence: 99%
“…The upstream diaphanous (DIAPH) genes accelerate actin nucleation and suppress actin depolymerization. Of interest, disruption of the DIAPH2 coding region was found in a POI family (31), whereas genome-wide association studies identified DIAPH2 (32) and DIAPH3 (33) as candidate genes in regulating follicle reserve and menopause (Fig. S7).…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic studies have suggested that the long arm of the X chromosome is mainly involved in defects of ovulation [Bione et al 1998]. To the best of our knowledge five genes were disrupted as a result of interruption by an X;autosome translocation near our critical region have been observed.…”
Section: Resultsmentioning
confidence: 96%
“…To the best of our knowledge five genes were disrupted as a result of interruption by an X;autosome translocation near our critical region have been observed. [Cremers et al 1990], and DIAPH2 (MIM * 300108) in Xq22 [Bione et al 1998]. However, most of the breakpoints mapped in the Xq region described in POF patients are intergenic [Mumm et al 2001;Prueitt et al 2002].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of deletions and translocations in POF1 and POF2 regions has suggested several POF-candidate genes, such as [36][37][38], although very few mutations have actually been detected in these loci [39,40].…”
Section: Candidate Genes On the X Chromosomementioning
confidence: 99%